EXPERIMENTAL STUDY OF 3D SELF-ASSEMBLED PHOTONIC CRYSTALS AND COLLOIDAL CORE-SHELL SEMICONDUCTOR QUANTUM DOTS - Pham Thu Nga; Vu Duc Chinh; Nguyen Xuan Nghia; Nguyen Viet Huy; Dao Nguyen Thuan; Pham Thai Cuong; Chu Viet Ha; Do Thuy Chi; Nguyen Nhu Dat; Le A Lan Anh; C. Barthou; P. Benalloul; M. Romanelli; A. Maître (Universitas Gadjah Mada, 2007)
In this contribution we present an experimental study of 3D opal photonic crystals. The samples are opals constituted by colloidal silica spheres, realized with self-assembly technique. The sphere diameter is selected in order to obtain coupling of the photonic band gap with the emission from CdSe/ZnS colloidal quantum dots. The quantum dots infiltrated in the opals is expected to be enhanced or suppressed depending on the detection angle from the photonic crystal. The structural and optical characterization of the SiO2 opal photonic crystals are performed by field-emission scanning electron microscopy and reflectivity spectroscopy. Measurements performed on samples permits to put into evidence the influence of the different preparation methods on the optical properties. Study of self-activated luminescence of the pure opals is also presented. It is shown that the luminescence of the sample with QDs have original QD emission and not due to the photonic crystal structure. The optical properties of colloidal core-shell semiconductor quantum dots of CdSe/ZnS which are prepared in our lab will be mention.